Gender relations on goat-farm household in Central Java, Indonesia - Handayani, Sri W. (Indonesian Journal of Animal and Veterinary Sciences, 1995)
This paper represents an attempt to examine gender relations in goat-farm households in Central Java . Guided by theory of farm household in which labor for household activities is supplied and organized based on gender and age differences of the household members . The study was conducted at Klirong village, sub-district Kebumen, Central Java in May 1995 . Twenty-four families who owned goats were chosen and divided into two groups based on the ownership to land . Participant observation method were used to collect information on the time spent for household maintenance activities, agricultural activities and on/off farm activities by household members . The results indicated that gender appears to be the primary determinant of labor and time allocation in two types of farm households . Since goat production is secondary economic activities for both type of households, therefore, the responsibility to take care of was allocated to the children, especially male children, while adults -- man and woman -- engage in the primary economic activities such as agricultural activities and selling labor for on/off farm activities . Key words: Gender relations, goat-farm households, participant observation method